Evaluation and Strengthening of Consciousness in Secondary School Students about Hygiene and Common Health Hazards (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Knowledge of hygiene and common health hazards is a must to know during schooling. It would be efficient to use a school as the basis of such public health activities, and it would also have a major impact on the community. But there is no record of such previous formal studies in our context. So objective of the present study was to search consciousness in secondary school students regarding health education. Materials and methods: It was a cross sectional observational study done in five schools. Of these schools, 100 high school students were selected by random lottery method during a period of six months from July 2023 to December 2023. Prior consent was taken from all the school authorities and students were all explained. A pretest was taken with a questionnaire by using Likert scale in some questions, where scoring was done from 1 to 5 and in some questions, in dichotomous style, scoring 1 for correct answer and 0 for wrong answer. After collection of data it was compiled and analyzed by SPSS 20. A posttest was also taken using the same questionnaire and the results were analyzed similarly. Results: Post intervention tests were higher than the pretest scores in all aspects. The mean pre-test score of 100 students of the five schools was 70.9900 with a standard deviation of 3.97846, the mean post-test score of that of was 94.0300, with a standard deviation of 1.20147. This increment in the score was highly significant (p value